Impacto económico del crimen en Colombia en delitos contra el patrimonio económico (1990-2012) (2016)
An approximation arises to quantify and then calculate the impact of crimes against the economic heritage – henceforth will be called DCPE - in Colombian economy, as a producer of income and employment. Supported in statistics of the estimated amount, in constant pesos of 2005, product of the commission of crimes against economic wealth from 1990 to 2012, due to the fact that the primary purpose of criminals dedicated to this activity, unlike other criminalconduct, is to obtain an economic profit that initially will take them to the satisfaction of their needs and those of their family circle. The idea, on the one hand, is to see if thecrime can be considered a “dynamic” player in an economy, as people involved in crime derive their income and their families’income from funds obtained illegally and on the other hand, as state and private legal activities related to protection and security that are incentivized or that its reason to be depends on the behavior of criminal activity. The criminal produces not only crimes but originates criminal law and many related activities (Marx, 1962, p 30-31).